Tuberculosis associates with both airflow obstruction and low lung function: BOLD results - F. S. Amaral, André; Coton, Sonia; S Kato, Bernet; C Tan, Wan; Studnicka, Michael; Janson, Christer; Gislason, Thorarinn; Mannino, David; D Bateman, Eric; Buist, Sonia; G J Burney, Peter; BOLD Collaborative Research Group (© 2015 European Respiratory Society, 2017)
This article was published in European Respiratory Journal [© 2015 European Respiratory Society] and the definite version is available at: http://erj.ersjournals.com/content/early/2015/06/24/13993003.02325-2014